Clinical significance of vascular endothelial growth factor expression in patients with carcinoma of the mouth floor and tongue - Broćić Miroslav; Kozomara Ružica; Cerović Snežana; Jović Nebojša; Vukelić-Marković Slobodanka; Stošić Srboljub (Vojnosanitetski Pregled)
Background/Aim. Although there are several types of malignant oral cancers, more than 90% of all diagnosed oral cancers are squamous cell carcinoma (OSCC). Angiogenesis is a cascade-like mechanism which is essential for tumor growth and metastasis. Therefore, vascular endothelial growth factor (VEGF) expression in OSCC and its effect on clinicopathological characteristics and prognosis is of major interest. So far researches have shown that increased expression of this gene, in other words enhanced synthesis of this protein (VEGF), independently on other factors, increases a chance for local relapse, and distant metastasis. Consequently, patients with OSCC have poor disease-free survival, as well as poor overall survival. The aim of the study was to determine clinical significance of VEGF expression in patients with stage II and III OSCC. Methods. This retrospective study analyzed 40 patients who had been operated for OSCC of their tongue and the mouth floor. Of these patients, some had stage II and III OSCC with histological grade, G1-G3 and nuclear grade Ng1-Ng3. Two high quality tissue samples were obtained and immunohistochemical expression of VEGF was quantitatively determined by using high microscope amplification. The value of VEGF expression of 20% was rated as significant expression, whereas tumor cells reactivation less than 20% was considered very low or no expression at all. The patients were followed up for a 3-year period. Results. The obtained results showed that 11 (17.5%) patients had VEGF expression less than 20% and 29 (82.5%) above 20%. A statistical significance was immanent with positive nodal status (p < 0.05) and disease stage (p < 0.05). No statistical correlation was found between the level of VEGF expression and histological and nuclear grade, tumor size, disease relapse or patients overall survival. Conclusion. In spite the controversy about the prognostic relevance of VEGF our results as well as the results of previous studies, suggest that the expression of VEGF is not reliable as a clinical parameter for the prognosis and disease outcome but it is one of the important factors for the disease progression.